Analysis Of The Factors That Influence The Incidence Of Low Birth Weight At The Purwodadi II Health Center - Wahyu Utami Ekasari; Dewi Sapta Wati; Sunarti (Jurnal Profesi Bidan Indonesia, 2023)
Background : One of the goals of child health efforts is to ensure the survival of children through efforts to reduce the mortality rate of newborns, infants, and toddlers. The most common cause of neonatal death in 2021 in Indonesia are Low Brirth Weight (LBW) conditions of 34.5% and asphyxia of 27.8%. Other causes of death include congenital abnormalities, infection, COVID- 19, neonatal tetanus, and others. Factors that influence the incidence of LBW are maternal factors including the presence of diseases experienced by the mother during pregnancy (pregnancy complications, one of which is due to anemia), maternal factors (geographical), namely maternal age and parity, social economic conditions, educational status of the mother. Purpose: to determine the factors that influence the incidence of low birth weight babies (LBW) Method: This research is a quantitative study using an observational analytic survey with a cross-sectional approach, with a sample size of 207 respondents. Bivariate analysis with Chi Square test. Results: The results of the analysis in this study showed that maternal age (OR = 1.836) and parity (OR = 0.950) were not risk factors for low birth weight in newborns, while the variable Hb level (OR = 15.782) and LILA size (OR = 9,538) is a risk factor for low birth weight.Conclusion: The results of this study are that the Hb level and LILA size in pregnant women are risk factors for low birth weight, while maternal age and parity are not risk factors for low birth weight babies